2018
DOI: 10.1108/ijcst-02-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the air permeability of elastic knitted fabrics and their assemblies

Abstract: Purpose The purpose of this paper is to evaluate the air permeability of knitted fabrics containing elastane fibre and their seams applying both the new approach based on fabric thickness measurement at different pressures and standard method. Design/methodology/approach Investigations were performed with commercially available eight polyester knitted fabrics containing different elastane yarn proportion. Bonded seams were laminated applying the urethane thermoplastic adhesive film of 0.175 mm thickness. Bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…2.2.1 Specimen preparation. The lengthwise fabric strips were cut to 20 mm×80 mm size from control textile samples for both bonding and sewing considering that the technology requirements had been discussed in the previous research (Daukantienė and Vadeikė, 2018). The type of stitches for sewn seams was chosen based on the general requirement for knitted garmentstheir seams should be highly elastic.…”
Section: Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2.1 Specimen preparation. The lengthwise fabric strips were cut to 20 mm×80 mm size from control textile samples for both bonding and sewing considering that the technology requirements had been discussed in the previous research (Daukantienė and Vadeikė, 2018). The type of stitches for sewn seams was chosen based on the general requirement for knitted garmentstheir seams should be highly elastic.…”
Section: Testing Methodsmentioning
confidence: 99%
“…Hand testing was performed with commercially available eight microfibers' polyester-knitted fabrics intended for sportswear (Table I). The detailed structure of the investigated textiles can be seen from the SEM images that have been published in the previous research article (Daukantienė and Vadeikė, 2018). The knitted materials selected for hand study are suitable for the manufacturing of active sport clothes applying both adhesive bonding and sewing technologies.…”
Section: Investigated Materialsmentioning
confidence: 99%
“…, 2013; Havelka et al. , 2015; Grujic and Geršak, 2016; Daukantiene and Vadeike, 2018; Mandal et al. , 2019; Cheng and Chen, 2019; Silina et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although most scholars have evaluated subjective comfort, most of them only analyzed pressure or heat-humidity comfort separately (Troynikov et al, 2013;Havelka et al, 2015;Grujic and Ger sak, 2016;Daukantiene and Vadeike, 2018;Mandal et al, 2019;Cheng and Chen, 2019;Silina et al, 2019;Uren and Okur, 2019;Lee et al, 2020;Vasile et al, 2021). When people wear clothes, comfort is not only caused by pressure or heat-humidity, which may be caused by some senses such as pressure, heat-humidity and even tactile.…”
Section: Introductionmentioning
confidence: 99%
“…Wardiningsih and Troynikov 19 determined the effect of fabric direction, fabric composition and number of fabric layers on pressure generated by sport compression garments. Virginija and Giedre 20 found that the air permeability of the investigated knitted fabrics depends not only on their structure parameters but also on the fabric seam type. Some scholars have also studied sports comfort, but they are only limited to pressure or thermal-humidity, and have not conducted systematic research.…”
mentioning
confidence: 98%